Pengaruh Pembiasaan Doa Harian Terhadap Perkembangan Nilai Moral Dan Agama Pada Anak Usia 4-5 Tahun Di Tk Yamassa Surabaya - Mufarocha, Rochmatun Nisa; Saleh, Nanang Rokhman; Shari, Destita; Machmudah, Machmudah (Universitas Muhammadiyah Surakarta, 2025)
This study aims to determine the effect of daily prayer habituation on the development of religious and moral values in children aged 4–5 years at TK Yamassa Surabaya. The background of this research is the increasing use of digital technology, which has led to a decline in social interaction and children's understanding of religious and moral values. Preliminary observations indicated that some children had not yet developed the ability to recite daily prayers properly due to inappropriate behavior. The research uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The sampling technique used was saturated sampling. Data collection was conducted through observation and documentation. Data analysis included descriptive analysis, Normality Test, Homogeneity Test, and t-Test using IBM SPSS version 30. The results of the descriptive analysis showed an average pre-test score of 9.60 and a post-test score of 16.05. The normality test (Shapiro-Wilk) indicated that the data were normally distributed, with a pre-test value of 0.087 and a post-test value of 0.116. The homogeneity test showed that the data were homogeneous with a value of 0.175 > 0.05. The t-test showed a significance value of 0.001 < 0.05, which means there is a significant effect of daily prayer habituation. Based on these results, it can be concluded that daily prayer habituation has an effect on the development of religious and moral values in children aged 4–5 years at TK Yamassa Surabaya. It is suggested that educators, schools, and future researchers be more innovative in developing daily prayer habituation through various activities.